OPTIMIZATION OF DILTIAZEM HYDROCHLORIDE NANOPARTICLES FORMULA AND ITS RELEASE KINETICS EVALUATION - WINARTI, LINA; SARI, LUSIA OKTORA RUMA KUMALA; NURAHMANTO, EKA DEDDY IRAWAN DWI; ROSYIDI, VIDDY AGUSTIAN; AMELIANA, LIDYA; BARIKAH, KUNI ZU’ AIMAH; ANJARANI, REGITA ARDIA (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to determine the optimum formula of diltiazem HCl-loaded chitosan nanoparticles due to variations in the speed and duration of stirring and evaluating the release kinetics in vitro using DDSolver. Methods: The method used to prepare nanoparticles is ionic gelation. The ionic gelation method involves an ionic cross-linking between cations on the backbone of chitosan and anion, such as sodium tripolyphosphate (Na TPP). Results: Stirring speed of 1200 rpm and stirring time of 2 h produce an optimum response. The optimum formula has an entrapment efficiency of 71.10%, a particle size of 110.2 nm, and a polydispersity index of 0.268. The dry powder of diltiazem HCl nanoparticles produced a drug loading of 66.14±1.71% and a yield of 34.07±0.73%. The FT-IR showed ionic interaction (cross-linking) between ammonium ions from chitosan and phosphate ions from Na TPP. Scanning electron microscopy (SEM) analysis showed a particle size of 150 µm, a spherical shape, and rough surface morphology. In vitro release profiles indicated prolonged release, which follows the Korsmeyer Peppas model. Conclusion: It can be concluded that increasing the speed and duration of stirring will improve drug entrapment and reduce the particles size variation. The dry nanoparticles release mechanism is by diffusion and matrix erosion.